Pianp deficiency links GABAB receptor signaling and hippocampal and cerebellar neuronal cell composition to autism-like behavior - Winkler, Manuel; Biswas, Siladitta; Berger, Stefan; Enkel, Thomas; Arnold, Bernd; Komljenovic, Dorde; Sticht, Carsten; Goerdt, Sergij; Bartsch, Dusan; Géraud, Cyrill (Molecular psychiatry, 2020)
Pianp (also known as Leda-1) is a type I transmembrane protein with preferential expression in the mammalian CNS. Its processing is characterized by proteolytic cleavage by a range of proteases including Adam10, Adam17, MMPs, and the γ-secretase complex. Pianp can interact with Pilrα and the GB1a subunit of the GABAB receptor (GBR) complex. A recent case description of a boy with global developmental delay and homozygous nonsense variant in PIANP supports the hypothesis that PIANP is involved in the control of behavioral traits in mammals. To investigate the physiological functions of Pianp, constitutive, global knockout mice were generated and comprehensively analyzed. Broad assessment did not indicate malformation or malfunction of internal organs. In the brain, however, decreased sizes and altered cellular compositions of the dentate gyrus as well as the cerebellum, including a lower number of cerebellar Purkinje cells, were identified. Functionally, loss of Pianp led to impaired presynaptic GBR-mediated inhibition of glutamate release and altered gene expression in the cortex, hippocampus, amygdala, and hypothalamus including downregulation of Erdr1, a gene linked to autism-like behavior. Behavioral phenotyping revealed that Pianp deficiency leads to context-dependent enhanced anxiety and spatial learning deficits, an altered stress response, severely impaired social interaction, and enhanced repetitive behavior, which all represent characteristic features of an autism spectrum disorder-like phenotype. Altogether, Pianp represents a novel candidate gene involved in autism-like behavior, cerebellar and hippocampal pathology, and GBR signaling.